The effect of psychrotrophic bacteria on the quality of UHT milk : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Microbiology, The School of Food and Advanced Technology, Massey University, Palmerston North, New Zealand - Zhang, Dong (Massey University, 2020)
The psychrotrophic bacterial contamination of raw milk is one of the key factors determining the quality of processed dairy products due to the heat-stable enzymes produced by these bacteria. However, routine testing of raw milk only tests for total culturable mesophilic bacteria, not specifically the psychrotrophic bacteria. Another limitation of routine testing is the lack of any indication of the non-culturable bacterial types present, which may also influence milk quality. Studying the impact of this un-cultural component is a challenge but being able to detect them is useful in relating their presence to milk quality. In Chapter 3, 16S rDNA high-throughput sequencing and MALDI-TOF MS were used to identify the culturable and non-culturable psychrotrophic bacteria population of NZ raw milk, which had not been done before. Both methods showed that 𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴 is the predominant genus while high-throughput sequencing revealed a more diverse population than MALDI-TOF MS. The combination of these two methods can provide us a better picture of the psychrotrophic bacteria population of raw milk compared with the traditional methods. A seasonal and regional variation in the psychotropic bacterial composition in raw milk was observed. This information is also valuable to the NZ dairy industry, to enable the selection of the best quality milk for specific applications. The aim of Chapter 4 was to investigate the effect of extended chilled storage on the diversity of psychrotrophic bacteria in raw milk under the genus and species levels. The results showed that the psychrotrophic bacterial composition of chilled enriched milk is less diverse than fresh raw milk. The proportions of different bacteria also changed. For example, 𝘗. 𝘧𝘳𝘢𝘨𝘪 was the predominant species in fresh raw milk while 𝘗. 𝘭𝘶𝘯𝘥𝘦𝘯𝘴𝘪𝘴 became the predominant species after 5 days of chilled storage. Changes in the microbial composition of raw milk to specific bacteria can potentially affect the quality of final milk products as different bacteria vary in their ability to produce enzymes that spoil milk. This chapter also evaluated the heat-stability of proteolytic and lipolytic enzymes from the psychrotrophic bacteria. The heat stability of the enzymes produced by some bacteria, such as 𝘈𝘤𝘪𝘯𝘦𝘵𝘰𝘣𝘢𝘤𝘵𝘦𝘳 species isolated from milk, has not been reported previously. To maintain the quality of dairy products, understanding the growth of 𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴 and their protease activity in raw milk before any heat treatment is important. In Chapter 5, six dominant 𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴 showing heat-stable protease activity from Chapter 4 were grown in TSB, Skim UHT milk, and Whole UHT milk at 7℃ for 7 days. There were higher levels of proteolytic activity in milk media compared to TSB, with the whole milk showing the highest level. This leads to a hypothesis that dairy ingredients influence protease activity. The proteolytic activity in TSB medium enriched with different dairy ingredients showed that the presence of milkfat increased proteolytic activity. This was an unexpected result, not reported previously. The results based on an azocasein method were further confirmed by zymographic analysis. Multiple and stronger bands were observed in whole milk compared with skim milk and other media. Stronger bands were also observed in TSB enriched with fat. This is the first report showing that milk fat can induce the protease activity of some 𝘗𝘴𝘦𝘶𝘥𝘰𝘮𝘰𝘯𝘢𝘴 strains. One of the key determinants of the quality of UHT milk is the quality of the raw milk used to manufacture this product. However, the definition of “quality” of raw milk is not well defined. Total bacterial count, somatic cell counts, and antibiotic levels do not necessarily relate to the amount enzyme-producing bacteria nor the heat resistance of the enzymes produced. The aim of Chapter 6 was to replicate the effect of specific, high protease enzyme producing bacteria in raw milk used for UHT milk manufacture and predict the shelf life from the numbers of these bacteria raw milk used for UHT milk manufacture. Bacterial isolates (both single and mixed isolates) showing heat-stable proteolytic activity and commonly found in raw milk were grown to different numbers (10⁴-10⁷ cfu/mL) in farm-fresh UHT treated milk then UHT treatment was repeated. The storage life of this product was monitored over different temperatures (20, 30, and 55℃) likely to be found in the supply chain for up to 9 months. The results provide, for the first time, a guideline for UHT manufacturers to predict shelf life based on the initial microbiological content of the raw milk. Improvements in selecting the high microbiological quality of raw milk may reduce economic loss in the dairy industry.
Figures are re-used with permission or under a Creative Commons Attribution License (CC BY).
Keywords: Raw milk; Microbiology; New Zealand; Psychrophilic bacteria; Milk; Quality; 310701 Bacteriology